2014
DOI: 10.1016/j.aoas.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pendimethalin, Trifluralin and Terbutryn on Lolium multiflorum growing with barley during pre-emergence stage

Abstract: Three herbicides, namely Pendimethalin, Trifluralin and Terbutryn were used to control the Italian ryegrass (Lolium multiflorum) associated with barley (Hordeum vulgare). The first herbicide Pendimethalin gave an effective control of L. multiflorum at doses as low as .125 kg a.i/ ha and few plants survived with rates 0.5 kg a.i/ha. Effects on barley were severe; at dose of 0.25 kg a.i/ha barley plants decreased by more than 50%. Trifluralin controlled ryegrass numbers up to 90% at 1 kg/ha and caused little dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The herbicide pendimethalin promoted control of 26 and 40% at seven and 21 DAT, respectively; but at 35 DAT no control of ryegrass plants was observed. The use of pendimethalin has already been described as having a L. multiflorum control greater than 90% with similar doses (500 and 1,000 g•ha -1 ) (Alshallash 2014) to those used in the present study. However, the authors carried out experiments in pots and under controlled conditions of temperature and humidity, with an application of pendimethalin six days after sowing and evaluation performed at 14 DAT.…”
Section: The Efficiency Of Ryegrass and Turnip Weeds Control By Herbi...supporting
confidence: 63%
“…The herbicide pendimethalin promoted control of 26 and 40% at seven and 21 DAT, respectively; but at 35 DAT no control of ryegrass plants was observed. The use of pendimethalin has already been described as having a L. multiflorum control greater than 90% with similar doses (500 and 1,000 g•ha -1 ) (Alshallash 2014) to those used in the present study. However, the authors carried out experiments in pots and under controlled conditions of temperature and humidity, with an application of pendimethalin six days after sowing and evaluation performed at 14 DAT.…”
Section: The Efficiency Of Ryegrass and Turnip Weeds Control By Herbi...supporting
confidence: 63%
“…The most popular and commonly used herbicides are not free of various flaws. Alshallash [22] reported that the length of oat, sorghum, and sugar beet roots was reduced after the treatment with pendimethalin. Moreover, the herbicide was also phytotoxic to soybeans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the herbicide was also phytotoxic to soybeans. When pendimethalin and trifluralin were used to control ryegrass ( Lolium multiflorum ) associated with barley ( Hordeum vulgare ) [22], a strong phytotoxicological effect on barley was observed. Both herbicides controlled well growth of Lolium multiflorum and the effect of pendimethalin on barley was very negative.…”
Section: Discussionmentioning
confidence: 99%
“…4 According to a recent report, about 14 million pounds of trifluralin was applied only in the USA in 2001. 10 Typically, trifluralin is administered to the soil to effectively manage various annual grasses and broadleaf weed species. 11 Its mechanism of action involves disrupting mitosis, which ultimately hinders root development and allows it to control weeds during their germination stage.…”
Section: Introductionmentioning
confidence: 99%